Optimizing Data Interoperability for System Efficiency: One Data Standard in the Government Environment - Wahyuni, Herpita; Mutiarin, Dyah; Pribadi, Ulung; Kumorotomo, Wahyudi; Arie Saputra, Herdin (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to determine the optimization of data interoperability for the efficiency of the One Data Employment System by analyzing the implementation of the One Data standard, technical challenges, organizational needs, and the benefits of strategic steps. This research uses a qualitative research approach with in-depth analysis assisted by NVivo 12 Plus Software with various data sources that support the research results, namely Previous studies/literature reviews, news, and websites on the Satu Employment Data portal. The results of the analysis show that the implementation of the One Data standard includes data collection and exchange policies, development of technological infrastructure, adoption of data standards, personnel training, and stakeholder involvement with inter-agency coordination, as well as regular data reporting and validation, are needed to prevent duplication. Technical challenges relate to differences in communication protocols, data formats, and security. The results of the implementation show that with a careful and collaborative approach, these technical challenges can be overcome, as seen from the network revitalization and increased data security at the Ministry of Manpower with the help of BSSN. Organizational needs by carrying out needs analysis, setting standards, developing infrastructure, and managing data quality. Benefit from strategic steps by aligning departments, training, and regular monitoring, as well as scalability and collaboration. One Employment Data organizers produce quality data through the coordination of various work units and one data policy.